A review of the mechanisms of abnormal ceramide metabolism in type 2 diabetes mellitus, Alzheimer’s disease, and their co-morbidities - Pan, Yun; Li, Jieying; Lin, Panjie; Wan, Lihua; Qu, Yiqian; Cao, Lingyong; Wang, Lei (Frontiers in Pharmacology, 2024)
The global prevalence of type 2 diabetes mellitus (T2DM) and Alzheimer's disease (AD) is rapidly increasing, revealing a strong association between these two diseases. Currently, there are no curative medication available for the comorbidity of T2DM and AD. Ceramides are structural components of cell membrane lipids and act as signal molecules regulating cell homeostasis. Their synthesis and degradation play crucial roles in maintaining metabolic balance in vivo, serving as important mediators in the development of neurodegenerative and metabolic disorders. Abnormal ceramide metabolism disrupts intracellular signaling, induces oxidative stress, activates inflammatory factors, and impacts glucose and lipid homeostasis in metabolism-related tissues like the liver, skeletal muscle, and adipose tissue, driving the occurrence and progression of T2DM. The connection between changes in ceramide levels in the brain, amyloid β accumulation, and tau hyperphosphorylation is evident. Additionally, ceramide regulates cell survival and apoptosis through related signaling pathways, actively participating in the occurrence and progression of AD.Regulatory enzymes, their metabolites, and signaling pathways impact core pathological molecular mechanisms shared by T2DM and AD, such as insulin resistance and inflammatory response.Consequently, regulating ceramide metabolism may become a potential therapeutic target and intervention for the comorbidity of T2DM and AD. The paper comprehensively summarizes and discusses the role of ceramide and its metabolites in the pathogenesis of T2DM and AD, as well as the latest progress in the treatment of T2DM with AD.